Role of Psychological Flexibility and Self-compassion in People on Home Parenteral Nutrition: Psychological, Line Care Adherence and Infection Outcomes - Sara Anne Rea; Victoria Marianne Samuel; Nuno Ferreira; Marc Owen Williams (Mediterranean Journal of Clinical Psychology, 2023)
Background: Home parenteral nutrition (HPN) is an often life-saving nutritional treatment. However, it requires meticulous adherence to line care procedures and poses challenges to daily activities which can impact a person’s quality of life (QOL) and psychological wellbeing. Less is understood about psychological processes that affect outcomes in HPN. Psychological flexibility (PF) and self-compassion (SC) have been identified as important processes in other chronic illness populations. This study aimed to examine the unique role of PF and SC in predicting psychological distress, wellbeing, QOL, line care adherence and line infections in adults on HPN.